Scaling up antivenom for snakebite envenoming in the Brazilian Amazon: a cost-effectiveness analysisResearch in context - Armand Zimmerman; Wuelton Monteiro; Joao Ricardo Nickenig Vissoci; Emily R. Smith; Thiago Rocha; Jacqueline Sachett; Fan Hui Wen; Catherine Staton; Charles J. Gerardo; Osondu Ogbuoji (The Lancet Regional Health. Americas, 2024)
Summary: Background: Snakebite envenoming (SBE) affects nearly three million people yearly, causing up to 180,000 deaths and 400,000 cases of permanent disability. Brazil's state of Amazonas is a global hotspot for SBE, with one of the highest annual incidence rates per 100,000 people, worldwide. Despite this burden, snake antivenom remains inaccessible to a large proportion of SBE victims in Amazonas. This study estimates the costs, and health and economic benefits of scaling up antivenom to community health centers (CHCs) and hospitals in the state. Methods: We built a decision tree model to simulate three different antivenom scale-up scenarios: (1) scale up to 95% of hospitals, (2) scale up to 95% of CHCs, and (3) scale up to 95% of hospitals and 95% of CHCs. We consider each scenario with and without a 10% increase in demand for antivenom among SBE victims. For each scenario, we model the treatment costs averted, deaths averted, and disability-adjusted life years (DALYs) averted from a societal, health system, and patient perspective relative to the status quo and over a time horizon of one year. For each scenario and perspective, we also calculate the incremental cost per DALY averted and per death averted. We use a willingness to pay threshold equal to the 2022 gross domestic product (GDP) per capita of Brazil. Findings: Scaling up antivenom to 95% of hospitals averts up to 2022 DALYs, costs up to USD $460 per DALY averted from a health system perspective, but results in net economic benefits up to USD $4.42 million from a societal perspective. Scaling up antivenom to 95% of CHCs averts up to 3179 DALYs, costs up to USD $308 per DALY averted from a health system perspective, but results in net economic benefits up to USD $7.35 million from a societal perspective. Scaling up antivenom to 95% of hospitals and CHCs averts up to 3922 DALYs, costs up to USD $328 per DALY averted from a health system perspective, but results in net economic benefits up to USD $8.98 million from a societal perspective. Interpretation: All three antivenom scale up scenarios – scale up to 95% of hospitals, scale up to 95% of CHCs, and scale up to 95% of hospitals and 95% of CHCs – avert a substantial proportion of the SBE burden in Amazonas and are cost-saving from a societal perspective and cost-effective from a health system perspective. Funding: W.M. and J.S. were funded by Conselho Nacional de Desenvolvimento Científico e Tecnológico (CNPq productivity scholarships). W.M. was funded by Fundação de Amparo à Pesquisa do Estado do Amazonas (PRÓ-ESTADO, call n. 011/2021-PCGP/FAPEAM, call n. 010/2021-CT&I ÁREAS PRIORITÁRIAS, call n. 003/2022—PRODOC/FAPEAM, POSGRAD/FAPEAM) and by the Ministry of Health, Brazil (Proposal No. 733781/19-035). Research reported in this publication was supported by the Fogarty International Center of the National Institutes of Health under Award Number R21TW011944. The content is solely the responsibility of the authors and does not necessarily represent the official views of the National Institutes of Health.